The Effectiveness of Interactive Game Use in Improving Cognitive Abilities of Children Aged 5–6 Years at TK Khairani - Jumiliati; Liza Fidiawati; Raudha Meutia (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The Effectiveness of Interactive Game Use in Improving Cognitive Abilities of Children Aged 5–6 Years at TK Khairani. Undergraduate Thesis. Early Childhood Teacher Education Study Program, Faculty of Teacher Training and Education, Bina Bangsa Getsempena University. Supervisor I: Liza Fidiawati, M.Pd. Supervisor II: Raudha Meutia, M.Ed. The This study aimed to determine the effectiveness of using interactive games in improving the cognitive abilities of children aged 5–6 years at TK Khairani, located on Medan–Banda Aceh Road, Lubok Batee Village, Ingin Jaya District, Aceh Besar Regency. Cognitive ability is an important aspect of early childhood development, including the ability to recognize numbers, understand simple arithmetic concepts, and solve problems. Therefore, innovative and engaging learning media are needed to support children's cognitive development. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The research was conducted in 2026 and involved 11 children aged 5–6 years as participants. Data were collected through observation using a cognitive ability assessment sheet and were analyzed using normality tests, homogeneity tests, and a Paired Sample t-Test with the assistance of SPSS software. The results showed that the average cognitive ability score increased from 6.18 in the pretest to 13.00 in the posttest. The Paired Sample t-Test revealed a significance value of 0.000 (p < 0.05) and a calculated t-value of -13.603, indicating a significant difference between the pretest and posttest scores. Based on these findings, it can be concluded that the use of interactive games is effective in improving the cognitive abilities of children aged 5–6 years at TK Khairani, Aceh Besar Regency